Effect of Catalyst Morphology on the Quality of CVD Grown Graphene. (22nd August 2013) - Hsieh, Ya-Ping; Wang, Yi-Wen; Ting, Chu-Chi; Wang, Hsiang-Chen; Chen, Kuang-Yao; Yang, Chang-Chung
Abstract : The strong interest in graphene has motivated large effort in the scalable production of high-quality material. The potential of chemical vapor deposition on Cu foil to produce such graphene is impeded by lacking understanding of the relation between catalyst properties and graphene performance. We here present a systematic analysis of the catalyst morphology and its effect on electrical properties of graphene. We find that nanometer sized particles increase the density of bilayer regions but have no significant effect on carrier transport. Long wavelength roughness (waviness), on the other hand, generates defective graphitic regions that deteriorate carrier mobility. These findings shed light on the graphene formation process on Cu substrates and open a route to improve graphene quality for electronics applications.